2002
DOI: 10.1093/jat/26.5.262
|View full text |Cite
|
Sign up to set email alerts
|

Excretion Profiles of Ethyl Glucuronide in Human Urine after Internal Dilution

Abstract: Ethyl glucuronide (EG) is a useful marker of alcohol consumption because its presence in urine can be detected up to five days. We investigated the impact of diuresis on the urinary excretion of EG, a minor ethanol metabolite. Seven healthy volunteers drank 250 mL of wine (25 g ethanol) in 15 min and, 240 min later, ingested 1 L of water within 15 min. Urine was voided before the drinking started and every 30-60 min for 400-550 min thereafter. Urinary ethyl glucuronide (UEG), creatinine, and ethanol were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
9

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 9 publications
1
43
0
9
Order By: Relevance
“…This was in accordance with an earlier study after the same dose of ethanol (n=6) (49), but lower than another study at a lower dose (n=7) (55). We further showed that somewhat less of the ingested ethanol was excreted as EtS (61) (not included in this thesis).…”
Section: Blood Kinetics Of Etg and Ets In Living Subjectssupporting
confidence: 92%
“…This was in accordance with an earlier study after the same dose of ethanol (n=6) (49), but lower than another study at a lower dose (n=7) (55). We further showed that somewhat less of the ingested ethanol was excreted as EtS (61) (not included in this thesis).…”
Section: Blood Kinetics Of Etg and Ets In Living Subjectssupporting
confidence: 92%
“…Normalisation of urinary EtG concentrations to a 100-mg/dl creatinine concentration was useful in an earlier work to compensate for urine dilution [19][20][21] and is commonly used for EtG concentrations in urine. In this study, the creatinine concentrations of every fresh urine sample at the beginning of the storage experiment (t 0 ) were measured.…”
Section: Resultsmentioning
confidence: 99%
“…Ethanol metabolism occurs primarily in the liver, mainly through oxidation catalyzed by alcohol dehydrogenases, aldehyde dehydrogenases, cytochrome P450 2E1, and catalase (Agarwal, 2001;Zakhari, 2006). Besides these pathways, glucuronidation by UDP-glucuronosyltransferases (UGTs) represents a minor detoxifying pathway for ethanol (,0.1% of complete alcohol elimination) (Jaakonmaki et al, 1967;Dahl et al, 2002;Goll et al, 2002). Ethanol itself is a good marker of alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%